The feeding location of three species herons Casmerodius albus, Egretta garzetta, and Bubulcus ibis in Pulau Dua Nature Reserve, Serang, Banten Province (Biodiversitas Journal of Biological Diversity, 2006)
This research is to know feeding location for three species herons that lived in Pulau Dua Nature Reserve (CAPD), Serang, Banten Province. This research has been done at feeding area for the herons around Pulau Dua Nature Reserve. The data were taken from film shooting use Focal Observation Methods, while the film shooting analysed use Scan Sampling Methods. Result showed that Casmerodius albus and Egretta garzetta were using the mudflat, fisheries and rice-fields around CAPD as feeding location. Bubulcus ibis was using ricefield and grassland as feeding location. The preference for C. albus to feeding in mudflat was (χ²=21691,29; db=2, α=0,01). E. garzetta have preference for feeding in fisheries (χ²=18221,27; db=2, α=0,01) and the preference for B. ibis to feeding in grassland is (χ²=27,57; db=1, α=0,01). The selections of feeding location for three species herons were depend on the specific preys for them. C. albus and E. garzetta were select fish as their food, and B. ibis choose insect and other small animals as his food. © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: feeding, location, herons, mudflat, rice-field, grass-land, fisheries.